Retrospective strategic analysis of LNTU brand management - Natalia Vavdiiuk; Natalia Koretska; Nadia Kovalchuk; Roksolana Gavrylyuk (Економічний форум)
Universities carry out educational activities in competitive conditions, and the growth of the value of the HEI brand will depend on its reputation. The potential for growth in the value of the HEI brand will include a decrease in overall competition; enhancing image and prestige; increase in financial resources; achieving the mission; achievement of the development strategy. Nowadays, there are many universities and colleges that manage their own brands to gain a competitive advantage. The increase in the number of new educational products leads to increased competition in the market of educational services. This requires higher education institutions to form brand management tools for the purpose of developing higher education in accordance with consumer needs and requests and maintaining communication with the audience The article examines the problems of brand management in higher education institutions. The relationship between the volume of enrolled students for study, financial income received from payment for educational services and the value of the OP brand was determined. The sub-brands of EP LNTU were distributed and a matrix of their positioning was formed. It has been established that the brand management of higher education institutions depends on the chosen strategy, and the effectiveness of strategy implementation depends on the evaluation of brand perception and vice versa. Strategic alternatives for managing OP sub-rents at LNTU (selective brand; prestigious brand; affordable brand; dead-end brand) and brand management tactics are proposed